Enforcement of Business Order by the Municipal Police in Pulogadung District under Jakarta Regional Regulation No. 8 of 2007 on Public Order - Manik, Martua; Hutauruk, Appe; Sihotang, Muhenri (Equality : Jurnal Hukum dan Keadilan, 2025)
This study aims to analyze the implementation of public order enforcement on specific business establishments operating in public spaces by the Municipal Police (Satpol PP) in Polugadung District, based on Regional Regulation of the Province of DKI Jakarta Number 8 of 2007 concerning Public Order. The research employs a normative-empirical legal method with a qualitative approach. Data were collected through document analysis, in-depth interviews with Satpol PP officers, local government officials, and business actors, as well as field observations. The findings indicate that although Regional Regulation Number 8 of 2007 provides a comprehensive legal framework, its implementation by Satpol PP remains suboptimal. Law enforcement tends to be limited to administrative measures such as warning letters and symbolic fines, without escalation to judicial proceedings. Key obstacles include regulatory overlap, limited personnel and operational resources, economic pressures on the community, and a communication approach that lacks participatory engagement. To improve legal compliance, a holistic strategy is required combining consistent repressive enforcement with preventive efforts such as participatory legal education, provision of affordable legal business locations, licensing reform, and institutional capacity strengthening within Satpol PP.